2023
DOI: 10.1093/intqhc/mzad048
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer care amidst a pandemic: a scoping review to understand the impact of coronavirus disease 2019 on health services and health outcomes

Abstract: Since the onset of the coronavirus disease 2019 (COVID-19) pandemic, health services for breast cancer (BC) have been disrupted. Our scoping review examines the impact of the COVID-19 pandemic on BC services, health outcomes, and well-being for women. Additionally, this review identifies social inequalities specific to BC during the pandemic. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews guidelines, the literature search was conducted using scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 114 publications
(239 reference statements)
0
1
0
Order By: Relevance
“…Indeed, prior data do indicate that among women diagnosed with breast cancer during and after the global pandemic, disruptions in screening and care are associated with worsening quality of life over time. 33…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior data do indicate that among women diagnosed with breast cancer during and after the global pandemic, disruptions in screening and care are associated with worsening quality of life over time. 33…”
Section: Discussionmentioning
confidence: 99%
“…Globally, breast cancer (BC) is one of the most common cancers in women; specifically in Ireland, BC accounts for one third of all major malignancies in women [5,6]. Studies from varying countries, including Ireland, have indicated that women with a diagnosis of BC experienced disruptions to their BC care including delays, cancellations, and modifications [7]. Women with BC have also been physically, emotionally, and psychosocially challenged, resulting in reduced quality of life (QoL) [8,9].…”
Section: Introductionmentioning
confidence: 99%